2022
DOI: 10.1002/esp.5356
|View full text |Cite
|
Sign up to set email alerts
|

Development of a geomorphic monitoring strategy for stage 0 restoration in the South Fork McKenzie River, Oregon, USA

Abstract: The South Fork McKenzie River (SFMR) in western Oregon, USA hosts one of the largest Stage 0 stream restoration projects implemented to date. Stage 0 refers to a multichannel planform with strong hydrologic connectivity to the adjacent floodplain and surface–subsurface connectivity. Stage 0 restoration was implemented on a 900‐m‐long reach of the SFMR by re‐grading the channel and floodplain using 65,000 m3 of sediment to raise the channel bed. Thousands of large logs were added and the ends of some logs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 61 publications
0
23
0
2
Order By: Relevance
“…Three studies combined aspects of longitudinal and lateral connectivity, either in the channel-floodplain (Hinshaw et al, 2022) or the catchment perspective (González-Romero et al, 2021;Turley et al, 2021). We deemed only one article to explicitly solely focus on lateral connectivity (Martini et al, 2022).…”
Section: Spatial Dimensionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies combined aspects of longitudinal and lateral connectivity, either in the channel-floodplain (Hinshaw et al, 2022) or the catchment perspective (González-Romero et al, 2021;Turley et al, 2021). We deemed only one article to explicitly solely focus on lateral connectivity (Martini et al, 2022).…”
Section: Spatial Dimensionsmentioning
confidence: 99%
“…Poeppl et al, In press). In this SI, five contributions have dealt with connectivity in mountain environments, with a specific focus on fluvial processes by Hinshaw et al (2022; South Fork McKenzie River basin, Cascade Mountains, Oregon, USA), Kemper et al (2022; Yampa River basin, Rocky Mountains, Colorado, USA), and Khan et al (2021; Richmond River catchment, Great Dividing Range, Australia), on hillslope processes by Martini et al (2022; Rio Cordon catchment, Italian Alps), or on both environments as shown by Turley et al (2021; Tahoma Creek catchment, Cascade Mountains, Washington, USA). Two papers investigated connectivity relationships in river and catchment systems (Bizzi et al, 2021: Vjosa River, Albania; González‐Romero et al, 2021: Segura River catchment, Spain), while two contributions had a specific focus on delta, estuary and wetland environments (Hiatt et al, 2022; Singh et al, 2022; Sonke et al, 2022).…”
Section: Environments and Geomorphic Process Domainsmentioning
confidence: 99%
See 3 more Smart Citations